Association of the interleukin-6 polymorphisms with systemic lupus erythematosus: a meta-analysis. (October 2015) - Cui, Y X; Fu, C W; Jiang, F; Ye, L X; Meng, W
Background: Interleukin (IL)-6, an important proinflammatory cytokine, plays a potential pathological role in systemic lupus erythematosus (SLE). Studies on the relationship of IL-6 gene polymorphisms with SLE are inconclusive. The aim of this study was to estimate the relationship more precisely. Methods: The databases of PubMed and Web of Science updated to 30 August 2014 were retrieved. Meta-analysis was conducted using allelic contrast, dominant, recessive and homozygote contrast models. Fifteen studies were included in this study and ethnicity-specific meta-analysis was performed on European, Iranian and Asian populations. Results: Analysis for the IL-6-174 G/C polymorphism under all models except the homozygote contrast model indicated an association in the overall population (allelic contrast model: odds ratio (OR) 1.428, 95% confidence interval (CI) 1.124–1.812, dominant model: OR 1.382, 95% CI 1.037–1.842, recessive model: OR 1.610, 95% CI 1.158–2.240, homozygote contrast model: OR 1.759, 95% CI 0.989–3.127), as well as in European individuals under all four genetic models (allelic contrast model: OR 1.557, 95% CI 1.155–2.098, dominant model: OR 1.699, 95% CI 1.203–2.400, recessive model: OR 1.506, 95% CI 1.176–1.930, homozygote contrast model: OR 2.118, 95% CI 1.103–4.065). Analysis for the IL-6-572 G/C polymorphism indicated significant association in overall ethnicities under the recessive model (OR 1.491, 95% CI 1.104–2.014), but not under other models or in Asian individuals. In addition, significant association between the IL-6-174 G/C polymorphism and discoid skin lesions and antinuclear antibodies (ANAs) were found under the allelic contrast model and recessive model, respectively (discoid skin lesions: OR 2.271, 95% CI 1.053–4.895; ANAs: OR 2.244, 95% CI 1.141–4.416). Conclusion: This meta-analysis provides evidence of the association between the IL-6 polymorphism and the risk of SLE, hinting that the IL-6-174 G/C and IL-6-572 G/C polymorphisms may play a role in SLE susceptibility.